FACING DIGITAL DISRUPTION: CORPORATE ADAPTATION STRATEGIES IN ECONOMY 5.0 - Reina A. Hadikusumo; Albert Budiyanto; Elisabeth Sudarmi (Adisam Publisher, 2025)
In the Economy 5.0 era, digital disruption is a significant challenge for companies in various sectors. This article explains the importance of an adaptation strategy to deal with rapid and complex technological change. Digital transformation is not only about adopting new technologies, but also involves changes in business operations and work culture. Upgrading employee skills through continuous training is a key factor in ensuring that the workforce remains relevant and competent. In addition, the development of a collaborative business ecosystem through strategic partnerships with technology startups, research institutions, and the government is identified as an important approach to creating innovation and added value. By implementing this strategy, companies can be more adaptive in facing the challenges of digital disruption and remain competitive in Economy 5.0.